Review Paper on Spam Detection Antiphishing Techniques - Namrata, Namrata (International Journal of Computer Sciences and Engineering, 2025)
Internet nowadays is very important share of our day to day life solving many problems on a daily basis. It turns out to be a helping hand to human in so many ways. Among the many advantages of internet, one is sharing of knowledge. Email is that application which is used by all to fulfill the purpose of sharing information. Our email inbox contains some mails which are not required or are unwanted or whose sender is not an authorized person. These types of mails are called the Spam. To detect the spam among the required mails is one kind of hectic task. So many methods have been implemented for this. A spam could be in the form of picture or text which is very harmful for the computer. Thus, Spam has been categorized into the category of problems which occurs frequently and should be handled by the internet user with the help of some better technique. A number of methods have been designed to overcome the issue of spam messages and mail. Already implemented techniques for spam detection have been described in this paper.